The Impact of Work Life Balance, Role Conflict and Work Overload on Employee Turnover Intention through the mediating role of Job Stress - Syed Majid Khalil; Sher Nawaz Khan; Dr. Fayaz Ali Shah (Journal of Business & Tourism, 2021)
The current study is to find out the impact of Work Life balance, Role Conflict and Work Overload on Employees Turnover Intention with the mediating role of job stress of Abdul Wali Khan University (AWKUM) of Khyber Pakhtunkhwa. Working in educational institutions is complex and dynamic in nature, therefore in these conditions employees faces many stresses. Referable to the most troubling of these fears the most affected relationship is the low performance of employees working in Abdul Wali Khan University (AWKUM) because of the stress. Different stressor in the management of universities like Work Life Balance, Role conflict and Work Overload are important determinants of stress. The workplace has some harsh realities, worldwide one of the basic challenges facing in an organization is their employee’s performance affected by stress. The employees who are working in different sectors of an organization have to deal with stress. Similarly, the university workers are among the same to deal with the stress. The performance of an organization is dependent on employee’s working ability and if the employees are in stress than their overall performance will be negatively affected, resulting in inefficiency and staff turnover. . To study stress in universities, the survey has conducted through a questionnaire designed by the Donald A Buckingham (2004) and KavithaVenugobal (2017). The questionnaire was sent to 300 respondents and 270 answered the questionnaire, which represents a response rate of 89.6%. Based on data collected, the correlation and regression of the variables were carried out in SPSS. The outcomes of the analysis show that Work Life Balance negatively affects the stress level of employees while Role Conflict and Work overload positively affect the job stress level of employees. As the job stress is the mediator in the study, its effect on employee turnover intention is positive. This study will help decision-makers to identify important stresses and see their impact on job stress.